Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Produk Pada Toko Ozie Sejahtera Di Jember : (Ditinjau dari Perspektif Ekonomi Syariah): Marketing Strategy Analysis to Increase Product Sales at the Ozie Sejahtera Store in Jember: (Viewed from a Sharia Economic Perspective) - Dewi, Beti Sari; Titisari, Purnamie; Yuliati, Lilis (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2023)
The purpose of this study was to identify and analyze marketing strategies to increase product sales at TokoOzie Sejahtera in Jember (Viewed from the Perspective of Islamic Economics). In this study, the informants were the owner, employees, and several consumers of Toko Ozie Sejahtera.The research method used in this research is qualitative by conducting interviews and making observations at the Ozie Sejahtera Shop. Field research procedures that produce descriptive data in the form of data from interviews and written data from the owners, employees and consumers of Toko Ozie Sejahtera.The results of this study stated that the strategy carried out by Toko Ozie Sejahtera was an Islamic marketing mix which contained 9 (nine) elements, namely product, price, place, promotion, people, process, physical evidence, promise, and patience; The most effective marketing strategies in increasing sales by Toko Ozie Sejahtera are product and location strategies. The products provided are many choices, many models and always follow current trends. A strategic location that makes it easier for the public to find the existence of Toko Ozie Sejahtera; and the strategy implemented by Toko Ozie Sejahtera is in accordance with sharia marketing which has 9 (nine) elements and also by applying the characteristics of the Islamic marketing mix, namely with the characteristics of rabbaniyyah, akhlaqiyyah, waqi'iyyah and insaniyyah.